Assessment of Molecular Imaging of Angiogenesis with Three-Dimensional Ultrasonography - Jason E. Streeter; Ryan C. Gessner; James Tsuruta; Steven Feingold; Paul A. Dayton (Molecular Imaging)
Molecular imaging (MI) with ultrasonography relies on microbubble contrast agents (MCAs) adhering to a ligand-specific target for applications such as characterizing tumor angiogenesis. It is projected that ultrasonic (US) MI can provide information about tumor therapeutic response before the detection of phenotypic changes. One of the limitations of preclinical US MI is that it lacks a comprehensive field of view. We attempted to improve targeted MCA visualization and quantification by performing three-dimensional (3D) MI of tumors expressing α v β 3 integrin. Volumetric acquisitions were obtained with a Siemens Sequoia system in cadence pulse sequencing mode by mechanically stepping the transducer elevationally across the tumor in 800-micron increments. MI was performed on rat fibrosarcoma tumors (n = 8) of similar sizes using MCAs conjugated with a cyclic RGD peptide targeted to α v β 3 integrin. US MI and immunohistochemical analyses show high microbubble targeting variability, suggesting that individual two-dimensional (2D) acquisitions risk misrepresenting more complex heterogeneous tissues. In 2D serial studies, where it may be challenging to image the same plane repeatedly, misalignments as small as 800 microns can introduce substantial error. 3D MI, including volumetric analysis of inter- and intra-animal targeting, provides a thorough way of characterizing angiogenesis and will be a more robust assessment technique for the future of MI.